Neutron cross-sections for advanced nuclear systems: the n_TOF project at CERN - Barbagallo M.; Mastromarco M.; Colonna N.; Altstadt S.; Andrzejewski J.; Audouin L.; Bécares V.; Bečvář F.; Belloni F; Berthoumieux E.; Billowes J.; Bosnar D.; et al. (EPJ Web of Conferences, 2014)
The study of neutron-induced reactions is of high relevance in a wide variety of fields, ranging from stellar nucleosynthesis and fundamental nuclear physics to applications of nuclear technology. In nuclear energy, high accuracy neutron data are needed for the development of Generation IV fast reactors and accelerator driven systems, these last aimed specifically at nuclear waste incineration, as well as for research on innovative fuel cycles. In this context, a high luminosity Neutron Time Of Flight facility, n_TOF, is operating at CERN since more than a decade, with the aim of providing new, high accuracy and high resolution neutron cross-sections. Thanks to the features of the neutron beam, a rich experimental program relevant to nuclear technology has been carried out so far. The program will be further expanded in the near future, thanks in particular to a new high-flux experimental area, now under construction.